New accountability in California through local control funding reforms: The promise and the gaps - Affeldt, John T. (Education Policy Analysis Archives, 2015)
California is in the midst of the nation’s most significant current overhaul of a state school funding and accountability system. This paper examines the state’s recent reforms enacted through the Local Control Funding Formula (LCFF) against the new accountability framework articulated by Linda Darling-Hammond, Gene Wilhoit, and Linda Pittenger in their August 2014 paper in this publication. There the authors addressed the need for states to align their accountability systems with new college and career-ready learning standards through “a focus on [1] meaningful learning, enabled by [2] professionally skilled and committed educators, and supported by [3] adequate and appropriate resources” (Darling-Hammond, Wilhoit, & Pittenger, 2014). Many key aspects of LCFF align California with the vision of a new accountability that promises to prepare the state’s students with 21st century college and career ready skills; other key building blocks must yet be put in place if California and its students are to realize the promise of the new paradigm.